Changes in the visual analyzer occurring as a result of space flight - M.A. Valyakh; N.G. Baeva (РМЖ "Клиническая офтальмология")
M.A. Valyakh1,2, N.G. Baeva1,2 1 City Clinical Hospital No. 15, Moscow, Russian Federation 2 Pirogov Russian National Research Medical University, Moscow, Russian Federation Nowadays, objectives of space medicine are to study the impact of space factors (microgravity, hypogravity, space radiation) on the human body, as well as to develop recommendations for improving the performance of crew members during space expeditions. Microgravity occurs while being at a great distance from celestial bodies when their gravitational influence is very small. And hypogravity, in turn, is a variant of reduced gravity. Over the past few years, NASA officers have repeatedly recorded changes in the visual organ of astronauts after long space missions, in particular, they manifested an optic nerve swelling, a reduction in the anterior-posterior axial length of the eye, a change in blood flow velocity, and hypermetropia. European scientists obtained similar data. Also, velvet-like exudates were ophthalmoscopically revealed and visual field loss was recorded. National scientists have reported a varying severity of optic nerve swelling in astronauts after long space missions. The article presents a structured review of the results of both foreign and national scientists as a result of astronaut survey during space missions and after their completion. Key words: microgravity, hypogravity, space flight, intraocular pressure, optic nerve swelling, hypermetropia, intracranial pressure. For citation: Valyakh M.A., Baeva N.G. Changes in the visual analyzer occurring as a result of space flight. Russian Journal of Clinical Ophthalmology. 2019;19(1):27–30. About the authors: 1,2Maxim A. Valyakh — ophthalmologist, assistant of the Department of Ophthalmology; 1,2Nadezhda G. Baeva — ophthalmologist; graduate student. 1City Clinical Hospital No. 15. 23, Veshnyakovskaya str., Moscow, 111539, Russian Federation. 2Pirogov Russian National Research Medical University. 1, Ostrovityanova str., Moscow, 117997, Russian Federation. Contact information: Maxim A. Valyakh, e-mail: maxvalyakh@gmail.com. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 14.11.2018.